2013
DOI: 10.3171/2012.10.spine12727
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating minimum clinically important difference for primary and revision lumbar fusion surgeries

Abstract: The MCID values were similar for the revision and primary lumbar fusion groups, even when subgroup analysis was done for different diagnostic etiologies, simplifying interpretation of clinical improvement. The results of this study further validate the use of patient-reported HRQOLs to measure clinical effectiveness, as a patient's previous experience with care does not seem to substantially alter an individual's perception of clinical improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 21 publications
0
37
0
1
Order By: Relevance
“…Similar to previous studies in both general[28, 29] and surgical populations [13, 30], which found a MCID of approximately five points, we calculated the MCID for PCS to be approximately four and MCS approximately six. While MCIDs are traditionally reported separately for PCS and MCS, the global assessment asks patients to rate their overall quality of life, not the physical or mental components.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Similar to previous studies in both general[28, 29] and surgical populations [13, 30], which found a MCID of approximately five points, we calculated the MCID for PCS to be approximately four and MCS approximately six. While MCIDs are traditionally reported separately for PCS and MCS, the global assessment asks patients to rate their overall quality of life, not the physical or mental components.…”
Section: Discussionmentioning
confidence: 60%
“…As a result, the minimum clinically important difference (MCID) for change in quality of life has been established for a range of specific surgical populations (approximately five points) [13, 14], but not for an unselected surgical population. Similarly, few studies have compared the change in quality of life across multiple surgical specialties.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of patients who reached the threshold for an MCID of 12.8 points2831 indicates that the change was not only statistically significant but also clinically significant. However, the MIS group experienced over four times greater improvement in ODI score (median 42 versus 9, respectively) and 82% of patients exceeded MCID values (versus 45% in the open group).…”
Section: Discussionmentioning
confidence: 98%
“…Minimal Clinically Important Difference (MCID) scores, a minimal threshold of clinically meaningful improvement that is distinguished from statistically significant improvement, were utilized for VAS neck, VAS back and ODI to estimate the effect size for the power analysis [24,25]. MCID values used in the power analysis were 2 points for VAS neck, 2 points for VAS back and 9 points for ODI [26,27]. For PSS-10, a difference of 7 in score was used as a conservative estimate of effect size for the power analysis [23].…”
Section: Discussionmentioning
confidence: 99%